Back calculation of shear strength of landslides in the Philippines - Del Rosario, Raphael C.; Domingo, Marc Vincent P.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
The main purpose of the research study is to back calculate the shear strength parameters of the recent landslides in the Philippines. The geographic profile of the Philippines is most adequate for this research having a wide variety of landscapes of variable slopes. A total of 4 slopes were analyzed in this study. Movement in the slope surface was considered as a failure having a factor of safety of 1. Given this assumption, shear strength parameters were back analyzed along with assumed geometric parameters using a slope stability analysis program, Slide 5.0 by Rocscience. For each site, different assumptions were made based on the available information and data. The range of the shear strength parameters for each site turned out to be the following: cohesion (c): 3-185N/m2 and internal friction angle (ϕ): 11º - 32º. Based on the obtained values, the back calculated shear strength parameters of all sites are in a reasonable range for use as baseline parameters in slope stability assessment as well as design of mitigation measures
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Landslides -- Philippines; Slopes (Soil mechanics) -- Stability